Strategi Pemerintah Korea Selatan Dalam Ekspor Industri Kreatif Tahun 2016-2018 - Choirin Nisa' Berliantika; Hermini Susiatiningsih; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
This research discussed about the strategy of the South Korean government to utilize the Korean wave in the export of its creative industries which include music, broadcasting (drama and films), animations, cartoons, and games, which are promoted by the South Korean government both domestically and internationally. This research focused on the implementation of the South Korean government’s strategy in spreading its creative industry to various countries to improve the South Korean economy through its exports. This research used a qualitative method with a descriptive type of research. The theory used in this research was the theory of national interest and public diplomacy. This research aims to describe that the South Korean government exported creative industries that contain South Korean cultural values with strategies, namely developing South Korea’s domestic potential, connecting South Korea with other countries, and making South Korea active in the international arena. These strategies have had an influence on the development of South Korea’s creative industry both in the domestic market and the international market, so that it has implications for export growth and improving the economy of the South Korean country.